Impact of corona and radio-frequency plasma treatment on the degradation of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) - Ana Antunes; Anton Popelka; Adriaan Stephanus Luyt; Abdelrahman Mahmoud; Omar Yosef Aljarod; Mohamed Hassan; Peter Kasak (eXPRESS Polymer Letters, 2022)
Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) is a polyester, produced naturally by microorganisms, with excellent biocompatibility. Corona and radio-frequency (RF) plasma treatment were applied in order to improve the degradation process of PHBV. Samples were subjected to an accelerated weathering test for 500, 1000, and 2000 h of weathering exposure and to natural weathering for one year. Various analytical, spectroscopic, and microscopic techniques have been used to analyze the degradation process. This study revealed that corona and RF plasma treatment acted as a hydrolytic and ultraviolet light (UV) degradation promoter for PHBV. Both plasma treatments chemically modify the PHBV surface resulting in better wettability contributing to the hydrolytic degradation. Microscopic analysis revealed a rougher defects-containing surface of plasma-treated PHBV in comparison with untreated PHBV after the degradation process, promoting deeper water diffusion and UV penetration. The photo- and hydrolytic degradation caused significant surface changes of plasma-treated PHBV after 2000 h of accelerated weathering and one year of natural weathering. Moreover, deterioration in mechanical properties has been more pronounced in the RF plasma-treated samples. These results demonstrate the potential use of plasma treatment on improving the degradability of PHBV.